The Role of Pre-operative Clinical Presentation and Quality of Life in Predicting Post-operative Satisfaction of the Elderly Patients Undergoing Knee Replacement Surgery in Hospitals Affiliated to Shiraz University of Medical Sciences-Iran - Gholamzadeh, Sakineh (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Knee replacement surgery is often successful; however, a number of patients are not satisfied with the results of the operation. Objectives: This study was designed to determine whether clinical presentation and quality of life (QoL) before knee replacement surgery could predict patient satisfaction with surgery. Materials and Methods: A cross-sectional study was performed among 250 elderly patients with the age of 60 years or over who were candidate for a unilateral knee replacement surgery in hospitals affiliated to Shiraz University of Medical Sciences. To gather data, the QoL Questionnaire, knee evaluation form, demographic, and satisfaction questionnaire were used. The questionnaires were filled-in before and after surgery and in follow-up time (2 months later). Results: Most of the respondents were women (66.4%) with the mean age of 68. 9 (standard deviation = 6. 84). The results showed a significant positive correlation between patients’ post-operative satisfaction and pre-operative clinical presentation (r = 0.195 P = 0.003) and QoL (r =156, P = 0.023). However, there was no significant association between post-operative satisfaction and pre-operative clinical presentation and QoL at follow-up time (P > 0.05). Linear regression analysis showed that pre-operation clinical presentations and QoL, respectively, explained 3.8% and 2.4% of the variance in post-operative satisfaction. Conclusions: The results showed that satisfaction after surgery in the elderly is partly influenced by the pre-operative QoL and clinical presentation. Therefore, for improvement of the patients’ post-operative outcomes, it is necessary to pay more attention to these variables in future planning.